2021
DOI: 10.1108/maj-07-2020-2745
|View full text |Cite
|
Sign up to set email alerts
|

Auditor ethics: do experience and gender influence auditors’ moral awareness?

Abstract: Purpose The purpose of this paper is to examine how experience and gender relate to the auditors’ moral awareness. Design/methodology/approach Hypotheses are informed by a neurocognitive approach to ethical decision-making and tested using survey data from 191 auditors of a Big Four audit firm in The Netherlands. Findings The main findings indicate that more experienced auditors (i.e. those with more years of work experience, a higher rank and a higher age) show higher levels of moral awareness. This posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Concerning work experience, Espinosa-Pike and Barrainkua (2016) found a positive and significant link between work experience and auditor ethical judgment. A recent study conducted by Carrera and Van Der Kolk (2021) found that more experienced auditors show higher levels of moral awareness. Other studies (i.e.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Concerning work experience, Espinosa-Pike and Barrainkua (2016) found a positive and significant link between work experience and auditor ethical judgment. A recent study conducted by Carrera and Van Der Kolk (2021) found that more experienced auditors show higher levels of moral awareness. Other studies (i.e.…”
Section: Resultsmentioning
confidence: 94%
“…Several studies (Carrera and Van Der Kolk, 2021; Adeel et al , 2021; Espinosa-Pike and Barrainkua, 2016; Dalton et al , 2014; Karacaer et al , 2009; Curtis, 2006; Karcher, 1996; Merchant and Rockness, 1994) examine the impact of personal auditor values (i.e. age, gender and experience) on auditor decision-making.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process involves the active participation of employees, aiming to implement technological processes successfully, as technology and digitalization have become integral aspects of modern business practices. A crucial aspect of examining the impact of digitization and digital transformation at the company level is considering the ethical context where ethical issues may vary depending on the various types of moral dilemmas (Carrera & Van der Kolk, 2021). Over the past decades, the role of ethics in business, particularly in digital business, has increased in significance (Paoloni et al, 2023), alongside numerous studies on how to foster strong ethical climates by making ethical decisions (Glover et al, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the upper echelons theory posits that personal characteristics affect decision‐making behaviours (Hambrick & Mason, 1984). Some studies document that audit judgements vary with auditor characteristics, such as auditor gender (Gold et al, 2009; Lee et al, 2019), auditor experience (Carrera & Van Der Kolk, 2021; Chi et al, 2017; Wang et al, 2015) and auditor expertise (Chin & Chi, 2009; Goodwin & Wu, 2014), resulting in variations in the quality of audited financial statements. In this paper, we focus on another kind of auditor characteristic, auditor overall experience measured by the length from the first time when auditors signed audited financial statements to the current year when the auditor signs reports.…”
Section: Introductionmentioning
confidence: 99%